Evaluating The Implementation of Solar Home Systems (SHS) In Sumba – East Indonesia - Yuan, Anita; Pinka, Daniel; Setyowati, Emerita (UI Scholars Hub, 2022)
The lowest electrification rate in Indonesia is in East Nusa Tenggara (NTT) province, leading to a high poverty rate and low education level. At the same time, NTT has higher solar irradiance than the Indonesian average, which can be used for electrification. In 2019-2021, seventeen (17) Solar Home Systems (SHS) were installed in churches with no electricity grid connection to address these challenges. These systems serve church community activities as well as learning centers for students. The first system design was improved and adopted in 2020 and 2021 to meet users’ needs better. However, the COVID-19 pandemic made it difficult to visit and monitor the first installations for around two years. Therefore, the attempt to evaluate the SHS project remains a challenge. In March 2022, surveys were conducted in this study to assess the SHS’ installation quality, the electrification situation, and how to improve existing and future SHS’ installations. The results show that the electrification ratio was increasing fast, and SHS has a positive economic impact compared to diesel generators. Furthermore, to improve its usability and decrease its failure, active service is key to increasing working SHS and improving its usage.